Breton & culture bretonne dans l’Éducation nationale - Yvon Evenou (La Bretagne Linguistique, 1992)
In 1992, the teaching of Breton language and culture in the French education system alone concerned about 10,000 students outside universities. This paper aims to provide an overview of the number of pupils at that time, both in primary and secondary schools. It also involves the teachers and the training offered to them to teach. Finally, it is necessary to talk about the objectives of this teaching and to sketch out future prospects for widening its scope.